Co-Governing Smart Cities Through Living Labs. Top Evidences From EU - Francesco BIFULCO; Marco TREGUA; Cristina C. AMITRANO (Transylvanian Review of Administrative Sciences, 2017)
Our purpose is to identify the relevance of participative governance in urban areas characterized by smart cities projects, especially those implementing Living Labs initiatives as real-life settings to develop services innovation and enhance engagement of all urban stakeholders. A research on the three top smart cities in Europe – i.e. Amsterdam, Barcelona and Helsinki – is proposed through a content analysis with NVivo on the offi cial documents issued by the project partners (2012-2015) to investigate their Living Lab initiatives. The results show the increasing usefulness of Living Labs for the development of more inclusive smart cities projects in which public and private actors, and people, collaborate in innovation processes and governance for the co-creation of new services, underlining the importance of the open and ecosystem-oriented approach for smart cities.